PENDAMPINGAN MASYARAKAT DALAM UPAYA PENGEMBANGAN POTENSI LOKAL KAWASAN PESISIR DESA TAMBOO KECAMATAN BONE PANTAI KABUPATEN BONE BOLANGO - Fenti Prihatini Tui; Juriko Abdussamad; Rosman Ilato; Rahmatiah Rahmatiah (LPPM Universitas Bina Bangsa, 2023)
This community service aims to develop the local potential of the coastal area for the people of Tamboo village, Bone Pantai sub-district, Bone Bolango Regency through mentoring activities in the form of socialization and workshops on strengthening the capacity of Bumdes and training in the manufacture of processed fish. The method of implementing activities is carried out through a participatory method approach, meaning that the community is placed as a subject in every activity starting from the planning, implementation and monitoring and evaluation stages. The results of implementing the activities are in the form of (1) increasing the understanding of Bumdes managers about the role and management of Bumdes, (2) increasing public knowledge about the diversification of processed fish which have high nutritional value and selling value so that they can increase the community's economic income